Pregabalin overdose causing sinus bradycardia – A rare complication - Kumar, Rajesh; Kumar, Jathinder; Malik, Ihtisham; Pate, Gordon (Journal of Cardiovascular Medicine and Cardiology, 2021)
We present the unique case of severe, symptomatic bradycardia associated with pregabalin overdose. Pregabalin is a widely prescribed drug not routinely associated with sinus bradycardia. A 39 year old male, presented having taken about 4g of pregablin with intention to self-harm. Following admission, he subsequently developed bradycardia on telemetry. Other possible causes were excluded with serial investigations. The bradycardia resolved by 96 hours without the need for temporary pacing. Patients presenting with pregabalin overdose should be monitored for bradycardia.